Pengaruh Model Pembelajaran Projek Based Learning Terhadap Minat Belajar Peserta Didik Di Kelas IX SMP Negeri 3 Satu Atap Taliabu Barat - Narto, Lestari Tari (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This experimental study aims to determine the effect of the Project-Based Learning (PjBL) model on student learning interest and to determine the extent of the increase in learning interest of 34 ninth-grade students at SMP Negeri 3 Satu Atap Taliabu Barat on the concept of light and optical instruments. The 34 students were divided into two groups: the experimental and control groups. This study was a quasi-experimental study using a nonequivalent control group design and a purposive sampling technique. The sample size was 17 students in the experimental group and 17 students in the control group. The instrument used was an objective essay test consisting of 10 questions with a score of 0-1. The results of this study were statistically tested using the IBM SPSS version 20 application program "t-test." Based on the calculation, the calculated t-value was 82.8824, while the t-table value was 56.1765. In accordance with the acceptance criteria, the results showed that the calculated t-value > t-table at a significance level of 0.05 for the post-test data. This is consistent with the hypothesis test and the questionnaire, which showed a student interest in learning of 13.6. Therefore, it can be concluded that the project-based learning model has an effect and increased students' interest in physics, particularly in the concepts of light and optical instruments.